Pelestarian Tradisi Baratan Kalinyamatan Jepara Pasca Pandemi - Farikhah Bella Sejati (UIN Imam Bonjol Padang, 2023)
This article aims to describe the preservation of the western traditions of Kalinyamatan Jepara after the pandemic. This research uses qualitative research methods, namely research that is presented descriptively by describing the events that occurred. This tradition is religious in nature and upholds Islamic teachings and respects local cultural traditions. Forms of the Western tradition include processions of offerings, reading tahlil, and praying together. The meaning of the Baratan tradition is as a form of self- purification to welcome the holy month of Ramadan, respect for Sultan Hadlirin, and a request for safety from Allah SWT. The pandemic caused western traditions to stop, because it was feared that they could spread widely, and western traditions began to be preserved after the pandemic in the spring and kriyan villages of Kalinyamtan Jepara. The function of the Western tradition is as a means of friendship, cultural preservation and tourism development. Keywords: Tradition; Baratan; Pandemic.